PENGARUH MODAL SENDIRI DAN VOLUME USAHA TERHADAP SISA HASIL USAHA PADA KOPERASI KECAMATAN TAPUNG HILIR - ", Murniasih; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study was conducted to examine the effect of own capital and business volume on net income in cooperatives Kecamatan Tapung Hilir Kabupaten Kampar. The data used in this study uses secondary data in the form of financial statements of the cooperative Kecamatan Tapung Hilir Kabupaten Kampar 2015-2019. Data collection method using documentation. Method of data analysis using multiple linear regression analysis, t test, f test, and coefficient of determination test using SPSS 25 device. The results of the analysis, it shows that the equity variable partially (t test) has a significant positive effect on net income and partially business volume (t test) has no effect on net income. Simultaneous results (f test) show that all independent variables have a significant effect on net income. The Adjusted R square value of 0,884 means that equity and business volume have an effect of 88,4% on net income. While the remaining 11,6% is influenced by other factorKeywords: Own Capital, Business Volume, and Net Income